FROM COMMAS TO COLONS : GUIDE TO FLAWLESS PUNCTUATION - adlina, nadhrah (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2024)
Punctuation is an essential tool in written communication that goes beyond mere symbols; it serves as the backbone for conveying clarity, coherence, and precision in text. examines the importance of proper punctuation in shaping the meaning and readability of written content. It provides an in-depth exploration of the most commonly used punctuation marks in the English language, such as commas, colons, semicolons, periods, quotation marks, parentheses, and hyphens. The article also addresses frequent punctuation errors that can lead to miscommunication or ambiguity, such as the misuse of commas or overuse of exclamation marks. By offering actionable tips and strategies, it empowers readers to avoid these pitfalls and write with greater confidence and accuracy. Additionally, the role of punctuation in enhancing professionalism, especially in academic, business, and digital writing, is emphasized, showcasing its impact on the perception of the writer's credibility and attention to detail.